PARENTS' INTERPERSONAL COMMUNICATION IN OVERCOMING ONLINE GAME ADDICT CHILDREN (Case Study at GPIB EBEN HAEZER BLITAR Church) - Naomi Mardiana; Andiwi Meifilina; Ferida Asih Wiludjeng (Universitas Islam Balitar, 2023)
Communication is the most essential thing in human relations, especially interpersonal relations in the family environment. Effective communication that exists between all family members can create togetherness and mutual understanding in the family, families must complement one another. Therefore, communication is very important in the family, especially to strengthen the relationship between parents and children. One form of communication in a family is interpersonal communication. The problem with this research is that the strong intensity of playing online games makes children indifferent to their surrounding environment. This is worth researching, because the problem of online game addiction can have a negative impact on children in the future. The formulation of the problem is how is the interpersonal communication process of parents in dealing with children who are addicted to online games and what is the impact of interpersonal communication of parents in dealing with children who are addicted to online games. This research aims to explain the interpersonal communication process of parents in dealing with children addicted to online games and the impact of explaining the impact of interpersonal communication between parents in dealing with children addicted to online games. This research uses a qualitative descriptive method and uses purposive sampling techniques in collecting informants. Data collection uses techniques: Interview, Observation, Documentation. The results of this research are interpersonal communication between parents in dealing with children who are addicted to online games using an aspect approach of openness, empathy, positive attitude.